A secret heir to secure his throne - Crews, Caitlin (Harlequin presents, 2023)
"Paris Apollo was unwillingly crowned king when his parents were murdered. Grief-stricken, he distanced himself from his people, intent on planning his revenge. Now he's discovered a shocking secret: he has a son! A legitimate heir would mean a triumphant return to power--if Madelyn Jones will marry him ... No longer wide-eyed and innocent, Madelyn refuses to be a pawn in Paris's royal game--but each electrifying moment in his presence reminds her of their first whirlwind affair. Dare she risk her heart again as his queen?"--Page 4 of cover.